The Gaussian integers
module commutative-algebra.gaussian-integers where
Imports
open import commutative-algebra.commutative-rings open import elementary-number-theory.addition-integers open import elementary-number-theory.difference-integers open import elementary-number-theory.integers open import elementary-number-theory.multiplication-integers open import foundation.cartesian-product-types open import foundation.dependent-pair-types open import foundation.identity-types open import foundation.sets open import foundation.universe-levels open import group-theory.abelian-groups open import group-theory.groups open import group-theory.semigroups open import ring-theory.rings
Idea
The Gaussian integers are the complex numbers of the form a + bi
, where
a
and b
are integers.
Definition
The underlying type of the Gaussian integers
ℤ[i] : UU lzero ℤ[i] = ℤ × ℤ
Observational equality of the Gaussian integers
Eq-ℤ[i] : ℤ[i] → ℤ[i] → UU lzero Eq-ℤ[i] x y = (pr1 x = pr1 y) × (pr2 x = pr2 y) refl-Eq-ℤ[i] : (x : ℤ[i]) → Eq-ℤ[i] x x pr1 (refl-Eq-ℤ[i] x) = refl pr2 (refl-Eq-ℤ[i] x) = refl Eq-eq-ℤ[i] : {x y : ℤ[i]} → x = y → Eq-ℤ[i] x y Eq-eq-ℤ[i] {x} refl = refl-Eq-ℤ[i] x eq-Eq-ℤ[i]' : {x y : ℤ[i]} → Eq-ℤ[i] x y → x = y eq-Eq-ℤ[i]' {a , b} {.a , .b} (refl , refl) = refl eq-Eq-ℤ[i] : {x y : ℤ[i]} → pr1 x = pr1 y → pr2 x = pr2 y → x = y eq-Eq-ℤ[i] {a , b} {.a , .b} refl refl = refl
The Gaussian integer zero
zero-ℤ[i] : ℤ[i] pr1 zero-ℤ[i] = zero-ℤ pr2 zero-ℤ[i] = zero-ℤ
The Gaussian integer one
one-ℤ[i] : ℤ[i] pr1 one-ℤ[i] = one-ℤ pr2 one-ℤ[i] = zero-ℤ
The inclusion of the integers into the Gaussian integers
gaussian-int-ℤ : ℤ → ℤ[i] pr1 (gaussian-int-ℤ x) = x pr2 (gaussian-int-ℤ x) = zero-ℤ
The Gaussian integer i
i-ℤ[i] : ℤ[i] pr1 i-ℤ[i] = zero-ℤ pr2 i-ℤ[i] = one-ℤ
The Gaussian integer -i
neg-i-ℤ[i] : ℤ[i] pr1 neg-i-ℤ[i] = zero-ℤ pr2 neg-i-ℤ[i] = neg-one-ℤ
Addition of Gaussian integers
add-ℤ[i] : ℤ[i] → ℤ[i] → ℤ[i] pr1 (add-ℤ[i] (a , b) (a' , b')) = a +ℤ a' pr2 (add-ℤ[i] (a , b) (a' , b')) = b +ℤ b' infix 30 _+ℤ[i]_ _+ℤ[i]_ = add-ℤ[i] ap-add-ℤ[i] : {x x' y y' : ℤ[i]} → x = x' → y = y' → x +ℤ[i] y = x' +ℤ[i] y' ap-add-ℤ[i] p q = ap-binary add-ℤ[i] p q
Negatives of Gaussian integers
neg-ℤ[i] : ℤ[i] → ℤ[i] pr1 (neg-ℤ[i] (a , b)) = neg-ℤ a pr2 (neg-ℤ[i] (a , b)) = neg-ℤ b
Multiplication of Gaussian integers
mul-ℤ[i] : ℤ[i] → ℤ[i] → ℤ[i] pr1 (mul-ℤ[i] (a , b) (a' , b')) = (a *ℤ a') -ℤ (b *ℤ b') pr2 (mul-ℤ[i] (a , b) (a' , b')) = (a *ℤ b') +ℤ (a' *ℤ b) infix 30 _*ℤ[i]_ _*ℤ[i]_ = mul-ℤ[i] ap-mul-ℤ[i] : {x x' y y' : ℤ[i]} → x = x' → y = y' → x *ℤ[i] y = x' *ℤ[i] y' ap-mul-ℤ[i] p q = ap-binary mul-ℤ[i] p q
Conjugation of Gaussian integers
conjugate-ℤ[i] : ℤ[i] → ℤ[i] pr1 (conjugate-ℤ[i] (a , b)) = a pr2 (conjugate-ℤ[i] (a , b)) = neg-ℤ b
The Gaussian integers form a commutative ring
left-unit-law-add-ℤ[i] : (x : ℤ[i]) → zero-ℤ[i] +ℤ[i] x = x left-unit-law-add-ℤ[i] (a , b) = eq-Eq-ℤ[i] refl refl right-unit-law-add-ℤ[i] : (x : ℤ[i]) → x +ℤ[i] zero-ℤ[i] = x right-unit-law-add-ℤ[i] (a , b) = eq-Eq-ℤ[i] (right-unit-law-add-ℤ a) (right-unit-law-add-ℤ b) associative-add-ℤ[i] : (x y z : ℤ[i]) → (x +ℤ[i] y) +ℤ[i] z = x +ℤ[i] (y +ℤ[i] z) associative-add-ℤ[i] (a1 , b1) (a2 , b2) (a3 , b3) = eq-Eq-ℤ[i] (associative-add-ℤ a1 a2 a3) (associative-add-ℤ b1 b2 b3) left-inverse-law-add-ℤ[i] : (x : ℤ[i]) → (neg-ℤ[i] x) +ℤ[i] x = zero-ℤ[i] left-inverse-law-add-ℤ[i] (a , b) = eq-Eq-ℤ[i] (left-inverse-law-add-ℤ a) (left-inverse-law-add-ℤ b) right-inverse-law-add-ℤ[i] : (x : ℤ[i]) → x +ℤ[i] (neg-ℤ[i] x) = zero-ℤ[i] right-inverse-law-add-ℤ[i] (a , b) = eq-Eq-ℤ[i] (right-inverse-law-add-ℤ a) (right-inverse-law-add-ℤ b) commutative-add-ℤ[i] : (x y : ℤ[i]) → x +ℤ[i] y = y +ℤ[i] x commutative-add-ℤ[i] (a , b) (a' , b') = eq-Eq-ℤ[i] (commutative-add-ℤ a a') (commutative-add-ℤ b b') left-unit-law-mul-ℤ[i] : (x : ℤ[i]) → one-ℤ[i] *ℤ[i] x = x left-unit-law-mul-ℤ[i] (a , b) = eq-Eq-ℤ[i] ( right-unit-law-add-ℤ a) ( ap (b +ℤ_) (right-zero-law-mul-ℤ a) ∙ right-unit-law-add-ℤ b) right-unit-law-mul-ℤ[i] : (x : ℤ[i]) → x *ℤ[i] one-ℤ[i] = x right-unit-law-mul-ℤ[i] (a , b) = eq-Eq-ℤ[i] ( ( ap-add-ℤ ( right-unit-law-mul-ℤ a) ( ap neg-ℤ (right-zero-law-mul-ℤ b))) ∙ ( right-unit-law-add-ℤ a)) ( ap (_+ℤ b) (right-zero-law-mul-ℤ a)) commutative-mul-ℤ[i] : (x y : ℤ[i]) → x *ℤ[i] y = y *ℤ[i] x commutative-mul-ℤ[i] (a , b) (c , d) = eq-Eq-ℤ[i] ( ap-add-ℤ (commutative-mul-ℤ a c) (ap neg-ℤ (commutative-mul-ℤ b d))) ( commutative-add-ℤ (a *ℤ d) (c *ℤ b)) associative-mul-ℤ[i] : (x y z : ℤ[i]) → (x *ℤ[i] y) *ℤ[i] z = x *ℤ[i] (y *ℤ[i] z) associative-mul-ℤ[i] (a , b) (c , d) (e , f) = eq-Eq-ℤ[i] ( ( ap-add-ℤ ( ( right-distributive-mul-add-ℤ ( a *ℤ c) ( neg-one-ℤ *ℤ (b *ℤ d)) ( e)) ∙ ( ap-add-ℤ ( associative-mul-ℤ a c e) ( ( associative-mul-ℤ neg-one-ℤ (b *ℤ d) e) ∙ ( ap ( neg-one-ℤ *ℤ_) ( ( associative-mul-ℤ b d e) ∙ ( ap (b *ℤ_) (commutative-mul-ℤ d e))))))) ( ( ap ( neg-ℤ) ( ( right-distributive-mul-add-ℤ (a *ℤ d) (c *ℤ b) f) ∙ ( ap-add-ℤ ( associative-mul-ℤ a d f) ( associative-mul-ℤ c b f)))) ∙ ( ( left-distributive-mul-add-ℤ ( neg-one-ℤ) ( a *ℤ (d *ℤ f)) ( c *ℤ (b *ℤ f)))))) ∙ ( ( interchange-law-add-add-ℤ ( a *ℤ (c *ℤ e)) ( neg-ℤ (b *ℤ (e *ℤ d))) ( neg-ℤ (a *ℤ (d *ℤ f))) ( neg-ℤ (c *ℤ (b *ℤ f)))) ∙ ( ap-add-ℤ ( ( ap-add-ℤ ( refl {x = a *ℤ (c *ℤ e)}) ( inv ( right-negative-law-mul-ℤ a (d *ℤ f)))) ∙ ( inv ( left-distributive-mul-add-ℤ a ( c *ℤ e) ( neg-ℤ (d *ℤ f))))) ( ( inv ( left-distributive-mul-add-ℤ ( neg-one-ℤ) ( b *ℤ (e *ℤ d)) ( c *ℤ (b *ℤ f)))) ∙ ( ap neg-ℤ ( ( ap-add-ℤ ( refl {x = b *ℤ (e *ℤ d)}) ( ( ap (c *ℤ_) (commutative-mul-ℤ b f)) ∙ ( ( inv (associative-mul-ℤ c f b)) ∙ ( commutative-mul-ℤ (c *ℤ f) b)))) ∙ ( ( inv ( left-distributive-mul-add-ℤ b ( e *ℤ d) ( c *ℤ f))) ∙ ( ap ( b *ℤ_) ( commutative-add-ℤ (e *ℤ d) (c *ℤ f)))))))))) ( ( ap-add-ℤ ( ( right-distributive-mul-add-ℤ ( a *ℤ c) ( neg-ℤ (b *ℤ d)) ( f)) ∙ ( ap ( ((a *ℤ c) *ℤ f) +ℤ_) ( left-negative-law-mul-ℤ (b *ℤ d) f))) ( ( left-distributive-mul-add-ℤ e (a *ℤ d) (c *ℤ b)) ∙ ( ap-add-ℤ ( ( commutative-mul-ℤ e (a *ℤ d)) ∙ ( ( associative-mul-ℤ a d e) ∙ ( ap (a *ℤ_) (commutative-mul-ℤ d e)))) ( ( inv (associative-mul-ℤ e c b)) ∙ ( ap (_*ℤ b) (commutative-mul-ℤ e c)))))) ∙ ( ( interchange-law-add-add-ℤ ( (a *ℤ c) *ℤ f) ( neg-ℤ ((b *ℤ d) *ℤ f)) ( a *ℤ (e *ℤ d)) ( (c *ℤ e) *ℤ b)) ∙ ( ap-add-ℤ ( ( ap-add-ℤ ( associative-mul-ℤ a c f) ( refl)) ∙ ( inv (left-distributive-mul-add-ℤ a (c *ℤ f) (e *ℤ d)))) ( ( ap-add-ℤ ( ( ap ( neg-ℤ) ( ( associative-mul-ℤ b d f) ∙ ( commutative-mul-ℤ b (d *ℤ f)))) ∙ ( inv (left-negative-law-mul-ℤ (d *ℤ f) b))) ( refl)) ∙ ( ( inv ( ( right-distributive-mul-add-ℤ ( neg-ℤ (d *ℤ f)) ( c *ℤ e) b))) ∙ ( ap ( _*ℤ b) ( commutative-add-ℤ (neg-ℤ (d *ℤ f)) (c *ℤ e)))))))) left-distributive-mul-add-ℤ[i] : (x y z : ℤ[i]) → x *ℤ[i] (y +ℤ[i] z) = (x *ℤ[i] y) +ℤ[i] (x *ℤ[i] z) left-distributive-mul-add-ℤ[i] (a , b) (c , d) (e , f) = eq-Eq-ℤ[i] ( ( ap-add-ℤ ( left-distributive-mul-add-ℤ a c e) ( ( ap neg-ℤ (left-distributive-mul-add-ℤ b d f)) ∙ ( left-distributive-mul-add-ℤ neg-one-ℤ (b *ℤ d) (b *ℤ f)))) ∙ ( interchange-law-add-add-ℤ ( a *ℤ c) ( a *ℤ e) ( neg-ℤ (b *ℤ d)) ( neg-ℤ (b *ℤ f)))) ( ( ap-add-ℤ ( left-distributive-mul-add-ℤ a d f) ( right-distributive-mul-add-ℤ c e b)) ∙ ( interchange-law-add-add-ℤ ( a *ℤ d) ( a *ℤ f) ( c *ℤ b) ( e *ℤ b))) right-distributive-mul-add-ℤ[i] : (x y z : ℤ[i]) → (x +ℤ[i] y) *ℤ[i] z = (x *ℤ[i] z) +ℤ[i] (y *ℤ[i] z) right-distributive-mul-add-ℤ[i] x y z = ( commutative-mul-ℤ[i] (x +ℤ[i] y) z) ∙ ( ( left-distributive-mul-add-ℤ[i] z x y) ∙ ( ap-add-ℤ[i] (commutative-mul-ℤ[i] z x) (commutative-mul-ℤ[i] z y))) ℤ[i]-Semigroup : Semigroup lzero pr1 ℤ[i]-Semigroup = prod-Set ℤ-Set ℤ-Set pr1 (pr2 ℤ[i]-Semigroup) = add-ℤ[i] pr2 (pr2 ℤ[i]-Semigroup) = associative-add-ℤ[i] ℤ[i]-Group : Group lzero pr1 ℤ[i]-Group = ℤ[i]-Semigroup pr1 (pr1 (pr2 ℤ[i]-Group)) = zero-ℤ[i] pr1 (pr2 (pr1 (pr2 ℤ[i]-Group))) = left-unit-law-add-ℤ[i] pr2 (pr2 (pr1 (pr2 ℤ[i]-Group))) = right-unit-law-add-ℤ[i] pr1 (pr2 (pr2 ℤ[i]-Group)) = neg-ℤ[i] pr1 (pr2 (pr2 (pr2 ℤ[i]-Group))) = left-inverse-law-add-ℤ[i] pr2 (pr2 (pr2 (pr2 ℤ[i]-Group))) = right-inverse-law-add-ℤ[i] ℤ[i]-Ab : Ab lzero pr1 ℤ[i]-Ab = ℤ[i]-Group pr2 ℤ[i]-Ab = commutative-add-ℤ[i] ℤ[i]-Ring : Ring lzero pr1 ℤ[i]-Ring = ℤ[i]-Ab pr1 (pr1 (pr2 ℤ[i]-Ring)) = mul-ℤ[i] pr2 (pr1 (pr2 ℤ[i]-Ring)) = associative-mul-ℤ[i] pr1 (pr1 (pr2 (pr2 ℤ[i]-Ring))) = one-ℤ[i] pr1 (pr2 (pr1 (pr2 (pr2 ℤ[i]-Ring)))) = left-unit-law-mul-ℤ[i] pr2 (pr2 (pr1 (pr2 (pr2 ℤ[i]-Ring)))) = right-unit-law-mul-ℤ[i] pr1 (pr2 (pr2 (pr2 ℤ[i]-Ring))) = left-distributive-mul-add-ℤ[i] pr2 (pr2 (pr2 (pr2 ℤ[i]-Ring))) = right-distributive-mul-add-ℤ[i] ℤ[i]-Commutative-Ring : Commutative-Ring lzero pr1 ℤ[i]-Commutative-Ring = ℤ[i]-Ring pr2 ℤ[i]-Commutative-Ring = commutative-mul-ℤ[i]